The possible effect of leprosy on marital and sexual relationships among women: a comparative exploratory study between women affected by leprosy, women with a visible physical impairment and able-bodied healthy women in the Eastern Terai region of Nepal - Banstola, Nandlal (NLR Nepal, 2014)
Summary Background Leprosy is a chronic infectious disease, caused by the Mycobacterium Leprae. The Mycobacterium Leprae can cause inflammatory reactions, resulting in damage of the peripheral nerves and skin. The damage of the nerves may affect the sensory, motor and autonomic functions of the nerves. Leprosy complications can cause facial deformities and deformities of limbs, as well as disabilities involving sight, touch and dexterity. Leprosy is one of the most stigmatized diseases known today and if left untreated, leprosy can lead to progressive physical, mental and social disabilities and dehabilitation. Social and psychological complications often may remain once the medical treatment is finished. Often, the psychosocial consequences a person has to bear after being diagnosed by leprosy, is heavier than the physical damage that may occur. The stigma surrounding leprosy can be a great burden and affects various dimensions of a person's life. Nepal is a known leprosy endemic country where leprosy is recognized as a public health problem. In Nepal, as in most cultures in the Global South, marriage is considered very important. In general, a good and stable marriage is associated with numerous benefits. Enjoying one's sexual relationship, something inseparably linked with marriage, is associated with selfconcept, emotional well-being and a sense of connectedness to the world and to a partner. Good marital and sexual relationships are however, especially for people affected by leprosy and people with a disability, not self-evident. Objective The research objective of this study is to explore the possible influence of leprosy on marital and sexual relationship among married women affected by leprosy in Nepal by comparing the differences in marital and sexual relationships between married women affected by leprosy, married women unaffected by leprosy with a visible physical impairment and married able-bodied healthy women in the Eastern region of Nepal. Methodology A qualitative approach was used. Participants were interviewed in-depth about their marital and sexual relationship by means of semi-structured interviews. Because of the specific selection criteria, participants were selected based on purposeful sampling. The participants were contacted through the Netherlands Leprosy Relief (NLR) network in Nepal and through local health posts. Three groups of people were included in the study: women affected by leprosy with and without visible impairments, non-leprosy-affected women with visible impairments, and able-bodied, healthy women. All women had to be married or have been married and had to be between the ages of eighteen and fifty years old. Exclusion criteria were women with a mental illness, widowed women and women whose husband did not know they have or have had leprosy. The interview guide and the actual interviews were pre-tested by means of pilot interviews. Taking into account the sensitive topic, participants were interviewed by a local, married female interpreter either in their home, or at a private, safe space near their home. The recordings were translated, transcribed and analyzed by using open coding and content analysis.